2017
DOI: 10.1111/apt.14038
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of the oesophageal squamous epithelium ‘normalisation’ process in patients with gastro‐oesophageal reflux disease treated with long‐term acid suppression or anti‐reflux surgery

Abstract: Five years of treatment is generally required before squamous epithelial cell morphology and proliferation are 'normalised' in patients with chronic GERD, despite endoscopic and symptomatic disease control. Control of the acid component of the refluxate seems to play the predominant role in restoring tissue morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(90 reference statements)
1
5
0
Order By: Relevance
“…We have read with great interest the editorial by Dr. Genta—an attempt to reconcile the short turnover time of the oesophageal squamous epithelium with the results of our study, which showed that complete “normalisation” of oesophageal histology takes at least a few years . The results obtained in the LOTUS study demonstrated that progressive improvement of oesophageal histology occurs over the course of 5 years, and the same phenomenon is observed with regard to the degree of epithelial proliferation assessed by Ki67.…”
Section: Proportions Of Successfully Treated Patients With Normal MIsupporting
confidence: 63%
See 2 more Smart Citations
“…We have read with great interest the editorial by Dr. Genta—an attempt to reconcile the short turnover time of the oesophageal squamous epithelium with the results of our study, which showed that complete “normalisation” of oesophageal histology takes at least a few years . The results obtained in the LOTUS study demonstrated that progressive improvement of oesophageal histology occurs over the course of 5 years, and the same phenomenon is observed with regard to the degree of epithelial proliferation assessed by Ki67.…”
Section: Proportions Of Successfully Treated Patients With Normal MIsupporting
confidence: 63%
“…A more accurate picture of the situation for individual patients can be deduced from Table . Although both groups of patients had no or mild lesions in more than 90% of cases at 5 years (ie, a finding not significantly different from that of a group of healthy controls), 9% of LARS patients and 6% of ESO patients, still showed severe histological lesions despite the absence of clinical failure.…”
Section: Proportions Of Successfully Treated Patients With Normal MImentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a degree of interobserver variability and discordance between severity of symptoms and microscopic changes, histology still plays a vital role in diagnosis as well as providing a platform for research purposes. Also, the results from the randomized control trial—LOTUS study concluded that histomorphology is a useful tool in the assessment of long‐term mucosal healing when comparing different therapeutic regimens and modalities …”
Section: Importance Of Histology In Gerdmentioning
confidence: 99%
“…Also, the results from the randomized control trial-LOTUS study concluded that histomorphology is a useful tool in the assessment of long-term mucosal healing when comparing different therapeutic regimens and modalities. 42,43…”
Section: Importance Of Histology In Gerdmentioning
confidence: 99%